2001
DOI: 10.1007/pl00001875
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Fibrin Glue in Treatment of Fistula in Ano

Abstract: Aim: This study was done to assess the efficacy and advantage of fibrin glue therapy in anal fistulae in comparison to conventional treatment. Patients and Method:The results of treatment of anal fistula by autologous fibrin tissue adhesive in 30 patients were compared with those obtained by conventional surgery in another 30 patients. All patients in both procedures had preoperative mechanical bowel preparations and preoperative intravenous antibiotic.The two groups were matched for age, sex, fistula type and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Fibrin glue application has been shown to be superior to conventional surgery in terms of patient comfort, undisturbed sphincteric function, reduced overall hospital stay, reduced postoperative analgesia requirement and faster return to normal activities, minimum operative trauma, and no complications. 4,11,12 Some studies that were performed using conventional surgery techniques reported fistula cure rates of from 44% to 78%. 12 However, the overall success rate was 83.3% in this study.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Fibrin glue application has been shown to be superior to conventional surgery in terms of patient comfort, undisturbed sphincteric function, reduced overall hospital stay, reduced postoperative analgesia requirement and faster return to normal activities, minimum operative trauma, and no complications. 4,11,12 Some studies that were performed using conventional surgery techniques reported fistula cure rates of from 44% to 78%. 12 However, the overall success rate was 83.3% in this study.…”
Section: Discussionmentioning
confidence: 98%
“…There are several possible explanations which may contribute to failures following sealing: the lack of fistulography to detect the extent of the fistula, a narrow communication between the fistula and the intestine that may still have been present, a short, straight tract making it impossible for the fibrin glue to be retained adequately in the tract for any length of time, technical problems because of lack of experience, and a failure of antibiotics to eradicate all bacteria trapped in the clots in the fistula. [3][4][5][6][7][8][9][10] There were eight recurrences in this study. It was suspected that in recurrent cases, the most probable causes were considered to be a relatively short fistula tract, technical problems, early oral intake postoperatively, and an infection in the tract.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The end-product is a gel-like substance that can be used in surgery to achieve homeostasis and a water-tight seal (Khafagy et al, 2001;Venkatesh & Ramanujam, 1999). The purpose of this study was to ascertain the effectiveness of a commercially available fibrin sealant (Beriplast ) in closing the conjunctival wound following strabismus surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Fibrin glue is a biological glue made up of fibrinogen and its multiple components [ 6 ]. The end product is a gel-like substance that can be used in surgery to achieve hemostasis and a water tight seal [ 7 ].…”
Section: Introductionmentioning
confidence: 99%